Centrally concentrated molecular gas driving galactic-scale ionized gas outflows in star-forming galaxies. Issue 3 (25th November 2020) - Hogarth, L M; Saintonge, A; Cortese, L; Davis, T A; Croom, S M; Bland-Hawthorn, J; Brough, S; Bryant, J J; Catinella, B; Fletcher, T J; Groves, B; Lawrence, J S; et al.
ABSTRACT: We perform a joint analysis of high spatial resolution molecular gas and star-formation rate (SFR) maps in main-sequence star-forming galaxies experiencing galactic-scale outflows of ionized gas. Our aim is to understand the mechanism that determines which galaxies are able to launch these intense winds. We observed CO(1→0) at 1-arcsec resolution with ALMA in 16 edge-on galaxies, which also have 2-arcsec spatial-resolution optical integral field observations from the SAMI Galaxy Survey. Half the galaxies in the sample were previously identified as harbouring intense and large-scale outflows of ionized gas ('outflow types') and the rest serve as control galaxies. The data set is complemented by integrated CO(1→0) observations from the IRAM 30-m telescope to probe the total molecular gas reservoirs. We find that the galaxies powering outflows do not possess significantly different global gas fractions or star-formation efficiencies when compared with a control sample. However, the ALMA maps reveal that the molecular gas in the outflow-type galaxies is distributed more centrally than in the control galaxies. For our outflow-type objects, molecular gas and star-formation are largely confined within their inner effective radius ( r eff ), whereas in the control sample, the distribution is more diffuse, extending far beyond r eff . We infer that outflows in normal star-forming galaxies may be caused by dynamical mechanisms that drive molecular gas into their central regions, which can result in locally enhanced gas surface density and star-formation.